Pelaksanaan Ganti Rugi Atas Tanah Masyarakat untuk Kepentingan Umum Berdasarkan Undang-Undang Nomor 2 Tahun 2012 (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze how the implementation of compensation for community land for public interest is based on Law No. 2 of 2012. This study uses an empirical normative method with a qualitative approach to obtain an in-depth analysis of the legal aspects and their implementation in the field. The types of data used in the study include primary data and secondary data. Data collection techniques used through observation, interviews and documentation. The data analysis technique used is the interactive model of Miles and Hubermen, which consists of data reduction, data presentation and data verification or drawing conclusions. The results of the study indicate that the implementation of compensation for community land in Kutambelin Village for public interest is not in accordance with the provisions of Law Number 2 of 2012 concerning Land Acquisition for Development for Public Interest. In practice, the land acquisition process is carried out without involving an independent appraisal institution, without formal deliberation on the compensation value, and using community donation funds instead of the government budget. And the inhibiting factors for the implementation of land compensation for the community in Kutambelin Village, Laubaleng District, Karo Regency include the low level of legal understanding among the community and village officials, the lack of socialization and education regarding land rights and compensation mechanisms, and the lack of effective coordination with authorized institutions such as the National Land Agency. The community's ignorance of legal rights, as well as the weak initiative of the village government to carry out the land acquisition process procedurally, have resulted in the community's right to obtain proper compensation not being fulfilled.